854. Long-term Outcomes of Participants on F/TAF for Pre-Exposure Prophylaxis: Results for 144 Weeks of Follow-Up in the DISCOVER Trial. (4th December 2021) - Ramgopal, Moti; Ruane, Peter; Shao, Yongwu; Ebrahimi, Ramin; Kintu, Alex; Carter, Christoph C; Das, Moupali; Baeten, Jared; Brinson, Cynthia; Shalit, Peter; Mounzer, Karam
Abstract: Background: In DISCOVER, a multinational randomized controlled trial, F/TAF demonstrated noninferior efficacy compared to F/TDF for HIV prevention with improved bone mineral density and renal safety biomarkers at the primary endpoint (when all participants had reached 48 weeks and 50% had reached 96 weeks) and at week (W) 96, the end of the blinded phase. We now report W144 outcomes for participants who were randomized to F/TAF and continued F/TAF in the open-label extension (OLE) phase. Methods: All participants who completed the randomized blinded phase could opt to receive F/TAF for at least 48 weeks in the OLE phase. We evaluated HIV incidence in participants on F/TAF through W144 and assessed changes in hip and spine bone mineral density (BMD) and in glomerular function (eGFR) from baseline to W144. Results: 2, 080 of the 2, 694 participants initially randomized to F/TAF opted into the OLE phase, and 1, 933 were still on study drug through W144, thereby leading to a total of 7, 885 person-years (PY) of follow-up on F/TAF. Eight participants taking F/TAF acquired HIV in the blinded phase and 3 in the OLE phase. Dried blood spot analyses on the 3 OL infections found tenofovir diphosphate levels consistent with low adherence. Genotypic resistance testing showed no relevant resistance mutations for the 3 new infections. Among participants taking F/TAF, HIV incidence was 0.16/100 PY (95% CI 0.06-0.33) at the primary endpoint, 0.16/100 PY (95% CI 0.07-0.31) through 96 weeks and 0.14/100 PY (95% CI 0.07-0.25) through 144 weeks. Participants taking F/TAF had increases in hip BMD (mean percentage change +0.54%) and in spine BMD (mean percentage change +1.02%) from baseline to W144 (Figure 1). Median eGFR increased over 144 weeks, with a median increase of 2.6 mL/min from baseline to week 144. Participants in the F/TAF arm gained a median 2.3 kg (IQR -0.9-5.8) over 3 years of follow up. Figure 1. Changes in hip and spine bone mineral density and in eGFR through Week 144 Conclusion: The OLE of DISCOVER allowed for a long-term assessment (144 wks.) of F/TAF for PrEP. HIV incidence remained low with BMD and renal function parameters remaining stable through 144 weeks of follow-up. These findings demonstrate that F/TAF is a safe and effective option for long-term use in people who would benefit from PrEP. Disclosures: Moti Ramgopal, MD FACP FIDSA, Abbvie (Scientific Research Study Investigator, Speaker's Bureau)Gilead (Consultant, Scientific Research Study Investigator, Speaker's Bureau)Janssen (Consultant, Scientific Research Study Investigator, Research Grant or Support, Speaker's Bureau)Merck (Consultant, Scientific Research Study Investigator)ViiV (Consultant, Scientific Research Study Investigator, Speaker's Bureau) Peter Ruane, MD, AbbVie (Consultant, Research Grant or Support)Allergan (Research Grant or Support)Gilead Sciences Inc. (Consultant, Research Grant or Support, Shareholder, Speaker's Bureau)Merck (Consultant, Research Grant or Support)ViiV Healthcare (Consultant, Research Grant or Support) Yongwu Shao, PhD, Gilead Sciences Inc. (Employee, Shareholder) Ramin Ebrahimi, MSc, Gilead Sciences Inc. (Employee, Shareholder) Alex Kintu, MD, ScD, Gilead Sciences Inc. (Employee, Shareholder) Christoph C. Carter, MD, Gilead Sciences Inc. (Employee, Shareholder) Moupali Das, MD, Gilead Sciences Inc. (Employee, Shareholder) Jared Baeten, MD, PHD, Gilead Sciences Inc. (Employee, Shareholder) Cynthia Brinson, MD, Abbvie (Scientific Research Study Investigator)BI (Scientific Research Study Investigator)Gilead Sciences Inc. (Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau, Personal fees)GSK (Scientific Research Study Investigator)Novo Nordisk (Scientific Research Study Investigator)ViiV Healthcare (Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau) Peter Shalit, MD, PhD, Abbvie (Grant/Research Support)Gilead Sciences (Consultant, Grant/Research Support, Speaker's Bureau)Glaxo Smithkline (Consultant, Grant/Research Support)Janssen (Consultant, Grant/Research Support, Speaker's Bureau)Merck (Grant/Research Support, Speaker's Bureau)Thera (Speaker's Bureau)ViiV Healthcare (Speaker's Bureau) Karam Mounzer, MD, Epividian (Advisor or Review Panel member)Gilead Sciences Inc. (Consultant, Scientific Research Study Investigator, Research Grant or Support, Speaker's Bureau)Janssen (Consultant, Research Grant or Support, Speaker's Bureau)Merck (Research Grant or Support, Speaker's Bureau)ViiV Healthcare (Consultant, Speaker's Bureau)